Evaluating PsychEd: a mental health and well-being educational programme for secondary schools. Issue 3 (May 2019) - Pittock, Alexandra; Meagher, Laura; Lawrie, Stephen M.
Abstract : Background: Young people's mental health and well-being is an important concern in the UK. Provision of education and support to schools has been highlighted as an area for improvement; however, evidence-based programmes are scarce and costly. Aims: To provide an acceptable education programme to improve pupils' confidence and knowledge of mental health and well-being. It covered the mental and emotional well-being outcomes set by the Scottish Government in their schools' curriculum. Method: Lessons were designed by A.P. and delivered by volunteer doctors and medical students, and supervised by a psychiatrist. Outcomes were measured using questionnaires before and after lessons with optional comments. Results: PsychEd was piloted in 2016 in six schools to pupils between the ages of 11 and 18. There was a statistically significant improvement in pupil confidence and knowledge after the lessons ( P < 0.001). Of the pupils 84% felt that having lessons on mental health was useful. Qualitative feedback was also collected and coded into positive, constructive and negative comments. In total, 72% of pupil comments were positive. Conclusions: PsychEd showed promising results. Future areas of development include reaching a greater number of local authority schools, longer training for volunteers and provision of teaching materials to teachers for their own use. Declaration of interest: None.